(untitled) (INTELLIGENCE Journal of Multidisciplinary Research, 2026)
This paper is about the functional and participatory relationship between local media and local governance in the context of Pokhara Metropolitan city. It explores how the local media particularly Samadhan National Daily and Adarsha Samaj National Daily contribute to process the role and responsibilities of local media in the context of new governing system . During this action, it follows the transparency, accountability, and citizen engagement within the local governance system. The study is grounded in the agenda-setting watchdog theories of journalism emphasizing the media’s capacity to monitor governmental performance at the grassroots level. Agenda Setting Theory is a communication theory developed in 1972 by MC Combs and Shaw. It explains the public perception and public support on something is shaped on the basis of agendas raised by the media . It means the most the issues is flowed by media the most the public believe that issue. The paper uses the descriptive and exploratory research design integrating qualitative and quantitative method including content analysis of published news items and in-depth interviews with local journalists and officials. Data were collected from the two leading daily newspapers of Pokhara over over one month. It is analyzed according to thematic categories such as governance, infrastructure, development and civic participation. As the findings reveal, the watchdog role of local media is comparatively underdeveloped. According to it, local newspapers actively disseminate developmental and local news but the numbers of investigative, critical analysis and in-depth stories are relatively less. Much of the coverage tends to be event-based or focused on official remarks only. The study concludes that the the local media’s capacity to strengthen democratic practice is significant but requires capacity building, professional autonomy, and institutional collaboration with local government. The paper contributes to the broader discourse on media governance in Nepal by emphasizing the importance of localized journalism in ensuring participatory democracy and sustainable development at the community level.